Saturation Time Characteristics of RO Membrane Skid to Clean Water Supply with Pressure Stage in Rejection. Issue 1 (February 2021) - Zakwan, Muhammad; Prayoga, Anton; Bismo, Setijo
Abstract: Reverse osmosis (RO) is one major water treatment process used to filter out the water pollution due to the Tsunami disaster in Pandeglang. This technology is applied where highly purified water is essential, including sea/groundwater desalination, boiler feed water filtering, product rinsing, laboratory testing, and biotechnology. However, RO requires advanced research to ascertain the method and optimum pressure of the multi-pass system needed to produce clean water through a membrane with a long saturation time. Therefore, this study employs RO multi-pass by varying pressure 6-3, 6-4, and 7-4 on the first and second stage to observe the effects of decreasing flux and TDS enhancement for 72 hours in Tanjung Lame village. The results showed more performance in producing potable water at pressure P1 = 6 bar/P2 = 3 bar compared to P1 = 6/P2 = 3, and P1 = 7/P2 = 4. Moreover, the total dissolved solids (TDS) known to satisfy clean water provision was estimated at 20 ppm, after the permeate in the first stage is used as feedstock in the second. Furthermore, applying P1 = 6 bar and P2 = 3 bar for the first and second stage produced the membrane saturation time in hours ranging between 72-80 and 72-131, respectively.